ANALISIS PENGGUNAAN KELAMBU BERINSEKTISIDA DI KABUPATEN TRENGGALEK TAHUN 2019 - Narsono Narsono; Yudied Agung Mirasa; Adelita Setiawan; Efi Sriwahyuni; Sunardi Sunardi (Universitas Fort De Kock, 2023)
Program development for the use of insecticide-treated nets aims to avoid mosquito bites/ prevent direct contact between humans and mosquitoes so that the chain of malaria transmission can be broken. To measure the success of program implementation, a survey is needed to determine the scope of using mosquito nets as well as the knowledge, attitudes and behavior of the community in supporting the program. This research used an observational study with a descriptive approach. The survey was conducted in Pandean Village, Trenggalek Regency in March - April 2019. Data collection was carried out directly through interviews with respondents using a questionnaire. Data analysis was carried out descriptively, presented in the form of tables and narratives. The results showed that 85.5% had used mosquito nets, 82.5% used insecticide-treated nets, 83.1% last night toddlers slept in mosquito nets, and 78.3% of toddlers slept in mosquito nets every night, as well as pregnant women Most of the 66.7% sleep in mosquito nets, as many as 85.5% of respondents know how malaria is transmitted, 63.5% know the benefits of using mosquito nets while sleeping. It can be concluded that respondents have used mosquito nets and know how malaria is transmitted, know the benefits of using mosquito nets, know how to install and when to install mosquito nets. The behavior of sleeping in mosquito nets for family members with a frequency of 5-6 nights a week, maintenance of mosquito nets is still not good but the condition of the mosquito nets is still good with no holes.Keywords: use of mosquito nets, insecticide-treated nets, behavior